Corroborar liegendes, invocar imatges, renovar la memoria i presentar models. El valor deis goigs en la religiositat valenciana durant la Contrareforma. - GOMIS CORELL, JOAN CARLES (Scripta, 2015)
This article applies the Panofsky's method to the analysis of "goigs" during the period of the Counter-Reformation in Valencia. It determines, regardless of their poetical form and melody, which the cultural function of these compositions was during that period, focusing on four different exemples. The underlying ideas are confronted to other contemporary cultural expressions (historical-texts, and devotional and hagiographical works and pictures). This establishes the interrelationship between cultural values of the joys and the society that generated them, and shows that were not naive expression of popular devotion but small and affordable versions of scholarly hagiographies and histories of images and therefore in order to have the same propaganda purpose.